2004
DOI: 10.1590/s0074-02762004000100018
|View full text |Cite
|
Sign up to set email alerts
|

Circulating filarial antigen in the hydrocele fluid from individuals living in a bancroftian filariasis area - Recife, Brazil: detected by the monoclonal antibody Og4C3-assay

Abstract: The purpose of this study was to examine the circulating filarial antigen (CFA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…A quantity of 1 mL of blood was filtered through a polycarbonate membrane 13 mL in diameter with 3-µm pores, as described by Rocha et al (2004).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…A quantity of 1 mL of blood was filtered through a polycarbonate membrane 13 mL in diameter with 3-µm pores, as described by Rocha et al (2004).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…This test, however, fails to detect Brugia malayi infection. For this, another test called the sandwich ELISA detects antibodies to the recombinant antigen Bm-SXP-1 is used [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the sensitivity of both parasitological and antigen tests decreases as the MF loads decrease 21,31,33,41 . This decrease may result in differential performance across population subgroups.…”
Section: Discussionmentioning
confidence: 99%